Memory of environmental conditions across generations affects the acclimation potential of scots pine. (12th February 2020) - Bose, Arun K; Moser, Barbara; Rigling, Andreas; Lehmann, Marco M.; Milcu, Alexandru; Peter, Martina; Rellstab, Christian; Wohlgemuth, Thomas; Gessler, Arthur
Abstract: Long generation times have been suggested to hamper rapid genetic adaptation of organisms to changing environmental conditions. We examined if environmental memory of the parental Scots pines ( Pinus sylvestris L.) drive offspring survival and growth. We used seeds from trees growing under naturally dry conditions (control), irrigated trees (irrigated from 2003 to 2016), and formerly irrigated trees ("irrigation stop"; irrigated from 2003–2013; control condition since 2014). We performed two experiments, one under controlled greenhouse conditions and one at the experimental field site. In the greenhouse, the offspring from control trees exposed regularly to drought were more tolerant to hot–drought conditions than the offspring from irrigated trees and showed lower mortality even though there was no genetic difference. However, under optimal conditions (high water supply and full sunlight), these offspring showed lower growth and were outperformed by the offspring of the irrigated trees. This different offspring growth, with the offspring of the "irrigation‐stop" trees showing intermediate responses, points to the important role of transgenerational memory for the long‐term acclimation of trees. Such memory effects, however, may be overridden by climatic extremes during germination and early growth stages such as the European 2018 mega‐drought that impacted our field experiment. Abstract : Environmental conditions (natural dry vs. irrigated) experienced by the mother trees of Pinus sylvestris significantly influenced the offspring's growth and survival, indicating that transgenerational environmental memory can shape trees' acclimation potential over the midterm to the long term.